Análisis costo-beneficio de la implementación de semáforos inteligentes en el sector urbano del Cantón Loja - Carrión Guerra, José Luis (2023)
This study focuses on the cost-benefit analysis of the implementation of intelligent traffic lights in the urban sector of Loja Canton, Ecuador. The problem addressed is the insufficient efficiency of vehicular and pedestrian traffic in the area, which has led to congestion, increased travel time, and problems with pollution and road safety. The lack of traffic regulation and the absence of traffic light systems have exacerbated these problems. The methodology used included a detailed quantitative analysis to calculate the total cost of the project, considering the acquisition of technology, installation, and operation. Projections of benefits were made, highlighting economic savings and improvements in road safety. The results indicate that the implementation of intelligent traffic lights would be economically viable and would provide long-term benefits. This study underscores the need to improve urban mobility and road safety in Loja Canton through the implementation of innovative technologies. The recommendations resulting from this analysis offer a solid foundation for future initiatives focused on positively transforming the quality of life of the inhabitants and optimizing the transport system in the urban area of Loja.